The Compliance level of fishing actors and their problems in The Coastal Fishing Port Sadeng to regulations - Risma Yudha Ariyantono; Ernani Lubis; Iin Solihin; Anwar Bey Pane (Bogor Agricultural University, 2020)
The Coastal Fishing Port Sadeng is located in Girisubo District, Gunung Kidul Regency, Yogyakarta. The Coastal Fishing Port Sadeng plays a role to support the development of marine fisheries in the Special Region of Yogyakarta Province. The initial information obtained was that at The Coastal Fishing Port Sadeng, fishing actors did not comply with licensing documents. The purpose of this study was to determine the problem and assess the level of compliance of fishing’s actors in The Coastal Fishing Port Sadeng, which has fishing vessels with a size of more than 5 GT, to the applicable regulations in the marine and fisheries sector. The method used in this research is a case study on the compliance of fishing vessels at The Coastal Fishing Port Sadeng. The data analysis used is descriptive analysis. The results of the study stated that the level of compliance of fishing vessels in Coastal Fishing Port Sadeng to the ownership of SIUP licensing documents was 97.14% (very good), SIPI 51.43% (very poor), SLO 48.57% (very poor), and SPB 31.43 % (very less). Licensing documents that are not owned or have expired and the incompatibility of documents with the physical ship are problems that cause the level of compliance of fishing business actors at Coastal Fishing Port Sadeng to be considered very low. Keywords: Compliance level, fishing business actors, problems, PPP Sadeng, regulations